Advances in accounting education teaching and curriculum innovations. Vol. 16 - Rupert, Timothy J. (Emerald, 2015)
Advances in accounting education: teaching and curriculum innovations publishes both non-empirical and empirical articles dealing with accounting pedagogy. All articles explain how teaching methods or curricula/programs can be improved. Non-empirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate. Volume 16 examines the following topics: intelligent online tutoring, creating a cheat-proof testing and learning environment, information literacy in the accounting curriculum and cost accumulation in small businesses.
Keywords: Accounting -- Study and teaching.; Finance -- Study and teaching.; elektronické knihy; electronic books